Observational research in U.S. classrooms : new approaches for understanding cultural and linguistic diversity - Waxman, Hersholt C.; Tharp, Roland G., 1930-2015; Hilberg, R. Soleste, 1959- (Cambridge University Press, 2004)
"The present national reform agendas stress that rigorous content and high expectations be accessible to all students, including students from groups whose achievement has traditionally lagged behind that of majority culture students. Improving achievement in U.S. schools, important for both social and economic stability, will require that instruction be responsive to our nation's increasingly diverse student population. This book includes theoretical frameworks as well as substantive research findings and provides examples of recently developed classroom observation instruments based on research on effective teaching practices for culturally and linguistically diverse students. Each chapter presents a new aspect of classroom observation research that will assist educators in their endeavors to improve U.S. schools."--Publisher's description